2002
DOI: 10.1159/000057675
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Diastolic Dysfunction in Healthy Pregnant Women

Abstract: Objective: The purpose of this study was to examine which hemodynamic parameters change under the natural volume overload of pregnancy. Study Design: 46 healthy pregnant women were echocardiographically examined during the course of pregnancy. To evaluate left ventricular diastolic function, mitral inflow and pulmonary venous flow profiles were used. Fractional shortening and left ventricular muscle mass were calculated. Results: In the course of pregnancy the left ventricular muscle mass index increased (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 18 publications
5
60
0
12
Order By: Relevance
“…As a consequence, the left ventricular response begins with an increase in heart rate which starts as early as from 1 st trimester, further increases during 2 nd trimester which is due to increase in venous return in spite of unchanged left ventricular ejection fraction during the entire course of pregnancy. 8,9 The present study strongly supports the above fact where higher heart rate values was observed in 2 nd and 3 rd trimesters of pregnancy when compared to control, which was statistically significant. Previous ECG studies have revealed widening of QRS complex, prominent S-wave in lead I and conspicuous Q-wave and inverted T-wave in lead III during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…As a consequence, the left ventricular response begins with an increase in heart rate which starts as early as from 1 st trimester, further increases during 2 nd trimester which is due to increase in venous return in spite of unchanged left ventricular ejection fraction during the entire course of pregnancy. 8,9 The present study strongly supports the above fact where higher heart rate values was observed in 2 nd and 3 rd trimesters of pregnancy when compared to control, which was statistically significant. Previous ECG studies have revealed widening of QRS complex, prominent S-wave in lead I and conspicuous Q-wave and inverted T-wave in lead III during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…The volume-overloaded state (with increased preload) of pregnancy causes physiological LVH;17 after the first pregnancy, subsequent pregnancies have been shown to enhance this 16. Similarly, as mentioned, the expected pregnancy-associated ST-segment sagging depressed the ‘Negroid pattern’ ST-segment elevation to the isoelectric line.…”
Section: Discussionmentioning
confidence: 89%
“…Although a cardiac output increase of different magnitude paralleled by a peripheral vascular resistance decrease has been well documented, [2][3][4][5][6][7][8][9][10][11][12] reports on cavity dimensions, mass, and volumes are inconsistent. [3][4][5][6][7][8][9][10][11][12] Likewise, myocardial function has been described as normal, depressed, or enhanced. 4,8 -13 Part of the differences might be explained by the different formulas used for deriving ejection fraction (EF).…”
Section: Editorial See P 283 Clinical Perspective On P 297mentioning
confidence: 99%